Early Changes in Striatal Activity and Motor Kinematics in a Huntington's Disease Mouse Model. Issue 10 (26th July 2022) - Koch, Ellen T.; Sepers, Marja D.; Cheng, Judy; Raymond, Lynn A.
ABSTRACT: Background: Huntington's disease is a progressive neurodegenerative disorder with no disease‐modifying treatments. Patients experience motor, cognitive, and psychiatric disturbances, and the dorsal striatum is the main target of neurodegeneration. Mouse models of Huntington's disease show altered striatal synaptic signaling in vitro, but how these changes relate to behavioral deficits in vivo is unclear. Objectives: We aimed to investigate how striatal activity correlates with behavior in vivo during motor learning and spontaneous behavior in a Huntington's disease mouse model at two disease stages. Methods: We used fiber photometry to record jGCaMP7f fluorescence, a read‐out of neuronal activity, in the dorsal striatum of YAC128 (yeast artificial chromosome‐128CAG) mice during accelerating rotarod and open‐field behavior. Results: Mice showed increased striatal activity on the rotarod, which diminished by late stages of learning, leading to an inverse correlation between latency to fall and striatal activity. The 2‐ to 3‐month‐old YAC128 mice did not show a deficit in latency to fall, but displayed significant differences in paw kinematics, including increased paw slip frequency and variability in paw height. These mice exhibited a weaker correlation between latency to fall and striatal activity and aberrant striatal activity during paw slips. At 6 to 7 months, the YAC128 mice showed significantly reduced latency to fall, impaired paw kinematics, and increased striatal activity while on the rotarod. In the open field, the YAC128 mice showed elevated neuronal activity at rest. Conclusions: We uncovered impaired motor coordination at a stage thought to be premotor manifest in YAC128 mice and aberrant striatal activity during the accelerating rotarod and open‐field exploration. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society